Presidential Influence on Police Practices: The U.S. President’s Indirect Impact on Fourth Amendment Case Outcome Through Supreme Court Appointments - Donner, Christopher M. (American journal of criminal justice, 2013)
Utilizing presidential influence theory as a conceptual framework, this study examines the extent to which U.S. presidents effect police practice case outcome through the Supreme Court justices they nominate. Through their confirmed nominees, presidents can have an enduring political impact long after they have left office. Results from a sample of 253 Fourth Amendment police practice cases from 1953–1997 demonstrate that presidents do have an indirect influence on police search and seizure practices. While presidents do not vote in Supreme Court cases, they still have an effect on case outcome because their appointees generally vote along similar ideological lines. Specific results, study limitations, and policy implications for law enforcement agencies are discussed.